The malformed Non-adult Human Skeletal Remains of the Anthropology Museum of Naples: reading the past writes the future - Borrelli, Lucia; Verderame, Mariailaria (Medicina Historica, 2022)
Human skeleton remains provide data to reconstruct the history of human evolution and allow to retrace the lifestyle, culture and habits of ancient and modern populations. Bones and teeth retain the traces of growth and aging processes and their morphology can be influenced by internal and external factors including metabolic, nutritional and infectious diseases or traumatic events. The skeleton therefore represents an interesting biological archive. In this study, by anthropometric and morphological analyses, we have examined the non-adult human skeletal remains of the Anthropology Museum of the University Federico II in Naples to derive information regarding the process of skull ossification and skeletal development during prenatal and neonatal life. Then we have crossed our results with those deriving from a bibliographic survey to determine if the observed malformed status met the criteria of any pathological diagnosis of genetic nature, possibly incompatible with life. The research was conducted through a non-invasive method to safeguard the integrity of finds considered their rarity and historic importance.